Influence of low air pressure on flame instability of methane buoyant laminar diffusion flames - Jinfei Zhao; Shengfeng Luo; Xuehui Wang; Dan Zhao; Jian Wang (Case Studies in Thermal Engineering, 2024)
This work experimentally investigated the buoyancy induced flame instability of laminar diffuison flames under different sub-atmospheric pressures (20kPa–100 kPa) in a reduced pressure chamber. Circular nozzle with inner diameter of 8mm was used to produced the laminar diffuison flames, and methane as one of the most commonly used renewable energies, was selected as the studied fuel gas. In this work, flame oscillation regime, flame oscillation amplitude, flame oscillation intensity and flame oscillation frequency were measured and analyzed. The experimental results show that first, for a given mass flow rate, a stabe laminar diffusion flame would transform into a Tip-flickering flame and then even a Bulk-flickering flame with increasing the air pressure. Such evolution was then interpreted physically and a dimensionless parameter was proposed for the purpose of determining flame oscillation regime. Second, The dimensionless flame oscillation amplitude can be non-dimentionlly correlated with a proposed dimensionless parameter, and a model for predicting the flame oscillation amplitude has been developed. Third, the flame oscillation frequency increased with increasing air pressure for a fixed mass flow rate. A global model for predicting the flame oscillation frequency under different sub-atmospheric pressures has been established.